THE IMPORTANCE OF TAX POTENTIAL IN THE FORMATION OF LOCAL BUDGET REVENUES - Sharipov Narzullo G‘ulomovich (Bright Mind Publishing, 2025)
The tax potential plays an important role in the formation of local budget revenues, as it is one of the main means of ensuring the financial independence of territories and increasing economic stability. Tax potential refers to the possibilities of attracting the economic resources available in the territory to the local budget by taxation. The article covers the mechanisms of full determination of tax potential in the formation of local budget revenues, expansion of the taxable base, identification of hidden economic activities and their involvement in taxation. Also, the emphasis is on the importance of local budgets to increase the number of objects subject to taxation by developing business entities in the regions, increasing production capacity, expanding service areas in order to strengthen the sources of income. At the same time, the article analyzes the possibilities of improving the activities of local tax authorities, increasing tax revenues through the use of modern information technologies. The effective use of tax potential helps to ensure stable financial resources of the local budget, provides the basis for the development of social infrastructure in the regions, expansion of the provision of quality services to the population.
Keywords: Local budget, tax potential, tax revenues, budget stability, tax base, economic potential, tax administration, hidden economy, tax policy, fiscal policy, tax benefits, tax burden.